Study on the Key Issues and Networking of Application Channel in the Case of IPv6 Transitory Technique Implementation - Jiexin Zhang; Wenhua Xu; Jianping Zhang (Dianxin kexue)
Some key issues of the application channel were analyzed in the case of IPv6 transitory techniques implementation. Then several networking plans were studied and tested based on different service models. Finally, relative solutions to the issues and implementation policies were provided.